UNPACKING THE TPACK FRAMEWORK IN EFL CONTEXT: A REVIEW OF EMPIRICAL STUDIES FROM 2015 TO 2019 - Shelia Anjarani (IdeBahasa, 2020)
Technological Pedagogical Content Knowledge (TPACK) has been implemented as a conceptual framework for the knowledge domains that teachers need to master to successfully teach using technology and it has attracted a lot of attention across the field of education. Nonetheless, the framework has been criticized for not being practically useful. TPACK studies were mostly conducted in Mathematics and Science. Meanwhile, research on integrating English as a foreign language (EFL) into TPACK has been lagging behind. To better understand the critics, an investigation of general characteristics of TPACK studies in EFL context is needed. This paper is a systematic literature review of 20 peer-reviewed journal articles concerning the use of TPACK in EFL context published from 2015 to 2019.